The impact of teaching approach on horse and rider biomechanics during riding lessons - Anna Byström; Agneta Egenvall; Marie Eisersiö; Maria Terese Engell; Sigrid Lykken; Susanne Lundesjö Kvart (Heliyon)
Riding relies on embodied and practical knowledge and is predominantly taught during practical lessons. Effective teaching is dependent on relevant instructions and evaluation from the riding teacher or trainer. The aim was to investigate how riding instructions affect horse and rider motion and rein tension during transitions between walk and trot.Two Swedish (S1, S2) and two Norwegian (N1, N2) riding teachers, and five riders per location participated. Each rider rode two horses, 40 lessons total. Videos, horse and rider kinematics and rein tension were recorded. The teachers were interviewed, teacher-student interactions were analysed using conversation analysis. Biomechanical data were analysed in mixed models.S1 and N2 spent about a third of their lessons preparing the students while S2 and N1 began with straight-line walk-trot transitions early on. With S1 and N2, maximum rein tension before and during down-transitions was lower than with S2 or N1. S2 and N2 focused relatively more on the walk, asking the riders to count each walk stride or focus on the rhythm. With S2, the timing between up-down movements of the withers and croup in walk was closest to the ideal 25 % (16–17 % vs. 8–14 % for the others, p < 0.05). With N2, horses showed the best walk hind limb protraction consistency (stride-to-stride difference 1.2–1.3° vs. 1.5–1.7°, p < 0.05).The results show that experienced riding teachers can have a consistent influence on a group of students and indicate that lesson design impacts rein tension. Experiences from this study can be used to inform teaching of riding, for the benefit of both riders and horse welfare.